Proceso de atención de enfermería en paciente con diabetes mellitus tipo 2 con complicaciones vasculares periféricas: un estudio de caso - Benitez Moran, Karla Paola (2024)
Currently, Type 2 Diabetes Mellitus (DM2) is a growing chronic disease that increases the risk of developing peripheral vascular complications, so the role of the nursing professional is key to its management and prevention. Diabetic foot is a common and serious complication of DM2, and nursing care in patients with this type of complication is critical to prevent and treat ulcers, infections, and amputations. This case study addresses the care of a 65-year-old DM2 patient with peripheral vascular complications, who was admitted with an infected lesion on the right foot and treated by surgical debridement and partial amputation. Nursing intervention focused on the wound healing process, infection prevention, and patient education in the management of her condition. Three key diagnoses were identified: impaired skin integrity, risk of infection, and poor knowledge of diabetes management. Interventions included wound cleansing, use of specific dressings, infection control, and education in self-care techniques and safe waste disposal. Wound evolution monitoring, performed with the TIME scheme, showed positive results: complete epithelialization and significant decrease in signs of infection. The patient's skin integrity improved, and his knowledge of diabetes management increased, thus reducing the risk of future complications. It also highlights the value of health education, prevention of complications, proper wound management and promotion of a healthy lifestyle, essential elements to improve the quality of life of these patients and prevent serious complications.